Fecal microbiota transplant rescues mice from human pathogen mediated sepsis by restoring systemic immunity - Sangman M. Kim (Nature Portfolio, 2020)
Sepsis due to multidrug resistant pathogens is the most common cause of death in intensive care units. Here, the authors report that fecal microbiota transplant (FMT) can rescue mice from lethal sepsis of pathogens isolated from stool of a critically ill patient and show that FMT reverses the immunosuppressive effect induced by the pathogen community.